MARKETING APPROACH OF OPERATIONAL STRATEGIES IN STU: A STUDY WITH REFERENCE TO KERALA SRTC - BINU B PILLAI and KURIAN JOSEPH
The economic and effective passenger transportation facility to the public in Kerala is doing by Kerala State Road Transport Corporation (KSRTC), the biggest single fleet owner. Various steps are envisaged to make KSRTC a healthy and competent organization to make the public service more efficient and effective despite it being in a serious debt trap. The article is summarizing the core concept of marketing in terms of service, its value, satisfaction, quality and their exchange, as the service product of State Transport Undertakings (STU) to be viewed beyond that of merely providing service from one origin to a destination but of facilitating consumers to meet their core needs such as attending work place, school, social functions etc. Their focus needs to be changed towards understanding customer preferences and designing marketing strategies to increase the customer base and market share. This paper attempts to apply the principles of marketing to transport operations and design marketing strategies for STUs using marketing tools available taking KSRTC as reference